Quantitative micro-scale flood risk assessment in a section of the Trotuș River, Romania - Țîncu, Roxana (2020)
This paper focuses on the estimation of direct damages caused by three flood scenarios with different return periods in the section Făgetul de Sus – Ghimeş – Palanca Pass of Trotuș River, with the aim of highlighting the need of improved land use plans. The damage for three land use classes (residential building, infrastructure and agriculture) were estimated using the damage curves developed by the European Joint Research Centre (JRC) as well as site specific maximum damage values. The data were processed with the help of the ArcMap 10.2 software and FloodRisk tool from QGIS software. Furthermore, the flood risk was assessed using the damage – probability curves, which associates the damage with the corresponding frequency of occurrence. This method was identified and adapted to the characteristics of the study area in order to develop a methodology of flood risk assessment that is answering the question: does the lack of land use plans increase the vulnerability and the flood damage? The results showed that the greatest damages are registered for the residential building land use class for a flood probability of 0.001. In this case the damages reach up to 60% on the scale range of deterioration factor, the total damage value being 2 million euros. For the same hazard probability the total registered damage value for roads is 7500 euro, for railways is around 12,000 euro, while for agriculture is around 84,000 euro. These results highlight the need of protection measures and land use plans development and implementation. Regarding the protection measures we consider that the egalitarianism would be the concept that should be applied in the study area and also an improved cooperation between government, specialized agencies and local authorities at local level would lead to a more efficient flood risk management process. The proposed methodology can be applied for micro-scale analysis, providing quantitative results regarding the flood damage and flood risk assessment. It includes a detailed vulnerability analysis of the elements-at-risk with the aim of developing a more comprehensive approach of flood risk assessment.